What factors of satisfaction and motivation are affecting the development of the academic career in Portuguese higher education institutions? - Machado-Taylor, Maria de Lourdes (2011)
An important constituent group and a key resource of higher education institutions (HEIs) is the faculty or academic staff. The centrality of the faculty role makes it a primary sculptor of institutional culture and has implications for the quality of the institution and therefore has a major role in achieving the objectives of the institution. Demand for academic staff in higher education has been increasing and may be expected to continue to increase. Moreover the performance of academic staff as teachers and researchers determines much of the student satisfaction and has an impact on student learning. There are many factors that serve to undermine the commitment of academics to their institutions and careers. Job satisfaction is important in revitalizing staff motivation and in keeping their enthusiasm alive. Well motivated academic staff can, with appropriate support, build a national and international reputation for themselves and the institution in the professional areas, in research and in publishing. This paper aims to identify the issues and their impacts on academic staff job satisfaction and motivation within Portuguese higher education institutions reporting an ongoing study financed by the European Union through the Portuguese Foundation for Science and Technology.